(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Researchers have been focusing on the family of distributions that includes the baseline distribution for some time now. In this paper, we use the transmutation method proposed by Shaw and Buckley (2007), to introduce an improved version of the Generalized Half-Logistic distribution Moments, moment generating function, quantile function, reliability analysis, order statistics, and Renyi entropy are just some of the distributional properties discussed here.The standard maximum likelihood method is employed to determine the distribution’s parameters.procedure.In the end, real-world examples demonstrate the distribution’s value sets.